Fracture resistances of heat-treated nickel-titanium files used for minimally invasive instrumentation - Yoo Jung Kang; Sang Won Kwak; Jung-Hong Ha; Gianluca Gambarini; Hyeon-Cheol Kim (BMC Oral Health)
Abstract Background This study compared the torsional resistance, bending stiffness, and cyclic fatigue resistances of different heat-treated NiTi files for minimally invasive instrumentation. Methods TruNatomy (TN) and EndoRoad (ER) file systems were compared with ProTaper Gold (PG). Torsional load, distortion angle, and bending stiffness were assessed using a custom device AEndoS, and toughness was calculated using the torsional data. Cyclic fatigue resistance was evaluated using another custom device (EndoC) with 45-degree curved canal in which file was rotated until fracture using dynamic pecking motion at 37 °C. One-way analysis of variance and Duncan’s post-hoc comparison were conducted at a significance level of 95%. Scanning electron microscopy (SEM) analyzed fracture features and differential scanning calorimetry (DSC) analyzed phase transformation temperatures. Results ER and TN showed significantly lower torsional strength than PG (p < 0.05). However, ER showed a significantly greater distortion angle and the highest toughness, followed by PG and TN (p < 0.05). Both ER and TN showed similar bending stiffness, which was lower bending stiffness than PG (p < 0.05). ER showed the highest cyclic fatigue resistance (p < 0.05). SEM revealed typical fracture features across all groups, with distinct milling grooves in PG and TN, not in ER. DSC indicated that PG and ER showed a peak of austenite (Ap) at temperatures higher than body temperature, 42 °C and 40 °C, respectively, while TN showed A p at 25 °C. Conclusion Files for minimally invasive instrumentations typically exhibited high cyclic fatigue resistance but showed differences in the properties. The selection should depend on the root canal and tooth condition.